PENGUATAN PERAN DAKWAH DALAM PELESTARIAN LINGKUNGAN HIDUP BERBASIS ECO-THEOLOGY DI DESA SENDANGIJO KECAMATAN SELOGIRI KABUPATEN WONOGIRI - M Mujiyati; Edy Muslimin; Zevana Asyam Zahran (AL HAZIQ: Journal of Community Service, 2026)
The partner community in Sendangijo Village (Selogiri District, Wonogiri Regency) faces persistent challenges in organic and inorganic waste management, unsustainable household farming practices, and limited integration of religious values with local environmental wisdom. The activity aimed to strengthen the role of da’wah—anchored in eco-theology—to improve resource-management practices, increase community participation, and enhance local food resilience. Implementation used a participatory mixed-methods design: thematic sermons at Masjid Al-Mu’minin, community workshops, accompaniment of KWT Dahlia, communal clean-up actions, seed distribution, and data collection via pre–post questionnaires, participant observation, attendance records, and FGDs. Outputs included a thematic study session (50 participants), KWT accompaniment, distribution of 100 eggplant seedlings, 100 chili seedlings, 2 date palms, and 10 avocado trees; preliminary findings indicate increased eco-theology understanding, greater intention to sort waste, and higher participation in communal work. The intervention shows promise in translating khalifah and anti-ifsād principles into local practice, but requires further quantitative impact measurement and systematic monitoring to confirm effect size and sustainability.